Recent Advances in Ionic Liquids - Muzibur Rahman, Mohammed (IntechOpen, 2018)
Recent Advances in Ionic Liquids contains research on the preparation, characterization, and potential applications of stable ionic liquids (ILs). ILs are a class of low- and stable-melting point, ionic compounds that have a variety of properties allowing many of them to be sustainable green solvents. It is promising novel research from top to bottom and has received a lot of interest over the last few decades. It covers the advanced topics of physical, catalytic, chemical, polymeric, and potential applications of ILs. This book features interesting reports on cutting-edge science and technology related to the preparation, characterization, polymerization, and potential applications of ILs. This potentially unique work offers various approaches on the R&D implementation of ILs or related ionic catalysts and their conjugates. With this in mind, the authors present R&D on the preparation, properties, potential applications, and utility of ILs. The chapters describe important applications in a wide variety of contexts, including polymerization, devices, electrochemistry, and biotechnology. Both the theoretical and practical, it can be passed from the stable as well as molten salt to the ionic liquid and vice versa. Experimental and theoretical techniques for examining these studies are elaborated based on the methods for preparation, utilization, applications, and analysis. This book epitomizes the transfer of these techniques and methods between the differing temperature regimes, and is a major contribution to the future of both fields. The book presents an overview of current ILs fundamentals: preparation, polymerization, substantial applications, and enhancement of research worldwide. The techniques of ILs preparation, total characterization, and possible applications related with ILs as well as modified or conjugated material research are investigated. It is hoped that it will be an important book for research organizations, governmental research centers, and academic libraries engaged in recent R&D of ILs.